KUALITAS INTERAKSI IBU-ANAK DALAM KAITANNYA DENGAN PERKEMBANGAN KEMAMPUAN BERGAUL ANAK USIA 4-5 TAHUN - KOMARIYAH, KOKOM (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract This research was aimed to relate the mother-child interaction quality among working mothers with the child’s interactive skill among 4-5 years old. The subject of this study are working mothers with the children aged 4-5 years old who are in the kindergarten in Kecamatan Depok Sleman Yogyakarta. The variables are the mother child interaction in the capability guidance aspect and the development of child interactive skill. The total sample is 136 person. The data were collected using questionnaire and observation and were analyzed by descriptive statistics and chi-square. The research showsthat the mother child interaction of the verbal, social, and fine motorcapability guiding aspect are in good level. The same was observed with the child’s interactive skill among 4-5 years old whose mother are working. The chi-square analysis shows that there is significant connection between interaction in the social guiding aspect and the fine skill with the child interactive skill, whereas in the verbal skill guiding aspect no significant connection with child’s interactive skill was observed,